2020
DOI: 10.35683/jcm20034.74
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y university students' intentions to become ecopreneurs : a gender comparison

Abstract: Recently, the worsening state of the natural environment has caused researchers and practitioners to rethink the way in which this issue should be solved. It has been argued that the solution should not simply be one of regulation but rather of innovation. As such entrepreneurship, or more specifically ecopreneurship, has been identified as a possible avenue to bring about pro-environmental transformation within the business sector. To date however, research within the field of ecopreneurship is still lacking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Green practices can be defined as actions that are environmentally friendly, and these may include reducing, reusing and recycling of used materials to minimise the amount of waste thrown away to protect the environment (Melay & Kraus, 2012;Russo, 2017;Strydom et al, 2020). Going green includes various components such as recycling, reducing, reusing, carbon neutral, preventing the wastage of materials, to name a few.…”
Section: Green Practices and Going Greenmentioning
confidence: 99%
“…Green practices can be defined as actions that are environmentally friendly, and these may include reducing, reusing and recycling of used materials to minimise the amount of waste thrown away to protect the environment (Melay & Kraus, 2012;Russo, 2017;Strydom et al, 2020). Going green includes various components such as recycling, reducing, reusing, carbon neutral, preventing the wastage of materials, to name a few.…”
Section: Green Practices and Going Greenmentioning
confidence: 99%
“…Industrial development, growing urbanization, and modern farming practices are among the activities [ 10 ]. Increase in pollution results from productivity expansion and economic growth has a detrimental impact on environmental deterioration and climate change [ 11 ]. Because it covers built-up land, CO 2 emissions, agricultural land, fisheries, pastures, and forest products [ 1 ], the ecological footprint is a more comprehensive assessment or measure than the CO 2 emission which is formerly employed as an environmental proxy most of the time [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the findings of Strydom et al (2020) have shown that students generally displayed positive intentions towards entrepreneurship and that male and female students had similar intentions towards entrepreneurship.…”
Section: Hypothesis 3 Entrepreneurial Education Is Positively Related...mentioning
confidence: 81%